Research Progress on Plant Polyphenols Regulating the Structure, Function, and Biological Characteristics of Dietary Proteins - Yuanyuan SUN; Xuchun ZHU; Hongzhi LIU; Xiaoyue ZHANG; Zhaowei HAN; Ning AN; Feiyue REN; Linyi ZHOU (Shipin gongye ke-ji)
Proteins are essential nutrients, while plant polyphenols exhibit beneficial properties such as anti-inflammatory, antioxidant, and protein quality-enhancing effects. The interaction between polyphenols and proteins varies based on the distinct compositions and structures of different polyphenols. This paper reviews recent studies on how polyphenols effect the structure, function, and biological properties of food proteins. Studies indicate that polyphenols interact with proteins through both non-covalent and covalent bonds. Non-covalent interactions primarily involve hydrogen bonding, hydrophobic forces, and electrostatic interactions. Covalent binding generally occurs under conditions such as heat, alkaline environments, or enzymatic reactions. These interactions typically disrupt the secondary structure of proteins, reducing the α-helical content while increasing β-sheet structures. This leads to the unfolding of the protein's tertiary structure and the exposure of hydrophobic groups. As a result of these interactions, proteins can undergo both aggregation and polymerization. Polyphenols may cause certain protein subunits to aggregate, while also forming small molecular polymers by binding to specific subunits. These changes can improve the emulsification and foaming properties of proteins, enhance their antioxidant and digestive functions, and reduce their allergenicity. The paper concludes by discussing challenges and future directions for research on polyphenol-protein interactions, aiming to provide valuable insights into how plant polyphenols can be used to enhance protein quality.